2009
DOI: 10.1089/met.2009.0023
|View full text |Cite
|
Sign up to set email alerts
|

Leisure Time Sedentary Behavior, Occupational/Domestic Physical Activity, and Metabolic Syndrome in U.S. Men and Women

Abstract: Background This study examines leisure time sedentary behavior (LTSB) and usual occupational/domestic activity (UODA) and the relationship with metabolic syndrome and individual cardiovascular disease (CVD) risk factors, independent of physical activity level. Methods NHANES 2003–2006 data from men (n=1868) and women (n=1688) with fasting measures were classified as having metabolic syndrome by the AHA/NHLBI definition. LTSB was determined from self-reported TV viewing and computer usage. UODA was self-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
120
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(135 citation statements)
references
References 25 publications
(40 reference statements)
11
120
1
3
Order By: Relevance
“…Simple measures such as reducing non-physical and sedentary activities; TV watching, video gaming or non-work related computer use to a limit of one hour per day, could potentially reduce the prevalence of CMS in the US adult population by 30-35% [70]. Sedentary living with low or no exercise leads to insulin resistance and secondary hyperinsulinemia, type II diabetes and the associated obesity, hypertension, hyperlipidemia and the ultimate common and undesired clinical outcome of atherosclerosis [105].…”
Section: Non-pharmacological Methods To Prevent Control or Reverse Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Simple measures such as reducing non-physical and sedentary activities; TV watching, video gaming or non-work related computer use to a limit of one hour per day, could potentially reduce the prevalence of CMS in the US adult population by 30-35% [70]. Sedentary living with low or no exercise leads to insulin resistance and secondary hyperinsulinemia, type II diabetes and the associated obesity, hypertension, hyperlipidemia and the ultimate common and undesired clinical outcome of atherosclerosis [105].…”
Section: Non-pharmacological Methods To Prevent Control or Reverse Cmentioning
confidence: 99%
“…In the United States, excessive television watching (average 2.2 hrs/ day) and non-working time computer use (1.7 hr./day) are accepted to have an association to the rising prevalence of CMS [69,70]. In a population-based study on 6,241, it was reported that with each hour/day of increased TV viewing, there was a 26% increase in CMS prevalence in women, while a total physical activity greater than 2.5 hrs/week was associated with reduction in the prevalence of insulin resistance and dyslipidemia in both genders and improvement in weight and BP control [71].…”
Section: Lack Of Exercisementioning
confidence: 99%
“…Sedentary time was recorded as the number of hours spent sitting or reclining at work, at home, or at school each day (excluding time spent sleeping) and was categorized as low (≤1 hour/ day), medium (2-3 hours/day), or high (≥4 hours/day) (20).…”
Section: Health-related Behaviorsmentioning
confidence: 99%
“…Possible contributors include genetic, environmental, psychosocial, cultural and unmeasured factors and many are not well clarified (Zaninotto et al 2007). It is clear that the observed ethnic differences in lipid profiles cannot be explained by genetics alone and may be more indicative of lifestyle-related factors such as dietary pattern and physical activity (Ruixing et al 2008;McNaughton et al 2009;Sisson et al 2009). To what extent is ethnic-specific lifestyle pattern associated with different lipid profiles deserves further investigation.…”
Section: Causes Of Ethnic Differencesmentioning
confidence: 99%